Intraoperative frozen section consultation by remote whole-slide imaging analysis –validation and comparison to robotic remote microscopy. Issue 6 (12th November 2019) - Menter, Thomas; Nicolet, Stefan; Baumhoer, Daniel; Tolnay, Markus; Tzankov, Alexandar
Abstract : Digital pathology including whole slide image (WSI) acquisition is a promising tool for histopathologic teleconsultation. To test and validate the use of WSI in comparison with robotic microscopy for intraoperative frozen section consultation of peripheral hospitals serviced by our department, we compared the VENTANA DP 200 slide scanner with an established remote-controlled digital microscope. Thirty cases were retrospectively analysed. In comparison with a median specimen handling time of 19 min using remote-controlled microscopy, the WSI handling was significantly shorter (11 min, p=0.0089) and offered better image quality, for example, allowing to detect a positive resection margin by a malignant melanoma that had been missed using the former system. Prospectively assessed on 12 cases, the median handling time was 6 min. Here, we demonstrate the applicability and the advantages of WSI for intraoperative frozen section teleconsultation. WSI-based telepathology prooves to be an efficient and reliable tool providing superior turn-around time and image resolution.